Critical approaches to Soweto poetry : dilemmas in an emergent literature - Karassellos, Michael Anthony (Department of English Language and Literature, 2016)
A review of contemporary South African and European critical approaches 'to "Soweto poetry" is undertaken to evaluate their efficacy in addressing the diverse and complex dynamics evident in the poetry. A wide selection of poetry from the 1970's and early 1980's is used to argue that none of the critical models provide an adequate methodology free from both pseudo-cultural or ideological assumptions, and "reader-grid"(imposition of external categories upon the poems).From this point of entry, three groups of critics with similar approaches are assessed in relation to Soweto poetry. The second chapter illustrates the deficiency in critical method- ology of the first group of critics, who rely on a politicizing approach. Their critique presupposes a coherent shift in the nature of Black Consciousness poetry in the 1970's, which is shown to be vague and problematic, especially when they attempt to categorize Soweto poetry into "consistently thematic" divisions. In the third chapter, it is argued that ideological approaches to Soweto poetry are impressionistic assessments that depend heavily on the subordination of aesthetic determinants to materialistic concerns. The critics in this second group draw a dubious distinction between bourgeois and "worker poetry" and ignore the inter- play between the two styles. Pluralized mergings within other epistemological spectrums are also ignored, showing an obsessive materialist bias. The fourth chapter examines the linguistic approach of the third group of critics. It is argued that they evaluate the poetry in terms of a defined critical terminology which assumes an established set of evaluative criteria exist. This is seen to be empiricist and deficient in wider social concerns. In the final chapter, it is submitted that each of the critical approaches examined foregrounds its own methodology, often ignoring the cohabitation of different systems of thought. In conclusion it is argued that a critical approach can only aspire to the formulation of a "black aesthetic" if it traces the mosaic of cultural borrowings, detours and connections that permeate Soweto poetry. Michel Serres, with his post-deconstructionist "approach", is presented as the closest aspirant. Bibliography: pages 117-123.